Cobalt-chromium-enriched medium ameliorates shear-stressed endothelial cell performance - Machado, Mariana Issler Pinheiro [UNESP]; Gomes, Anderson Moreira [UNESP]; Rodrigues, Marcel Ferreira [UNESP]; Silva Pinto, Thais [UNESP]; Fernandes, Célio Junior da Costa [UNESP]; Bezerra, Fábio J. [UNESP]; Zambuzzi, Willian Fernando [UNESP] (Elsevier, 2019)
Angiogenesis is a relevant mechanism to be considered for the success of bone healing, even considering endosseous implantable devices, providing adequate delivery of substances necessaries for the cell viability and bone de novo deposition. Within of the repertory of metal-based implantable alloys, cobalt-chromium (CoCr) has emerged with very interesting properties for biomedical applications. Additionally, we have shown that released molecules from implants devices are able to modulate cells away and because that we hypothesized these released molecules might act on endothelial cells. In order to better address this issue, we investigated the effect of Co-Cr-enriched medium on endothelial cells (HUVECs), considering a biological model subjecting those cells to shear-stress to partially mimic the physiological environment and further allow investigating intracellular pathways responsible to drive cytoskeletal rearrangement, cell viability and extracellular matrix (ECM) remodeling processes. Considering the analysis of the metalloproteinases (MMPs) activities, our data indicates an intense ECM remodeling in response to CoCr-enriched medium suggesting some role on angiogenesis once ECM remodeling is prerequisite to cell growth. This was better addressed by revealing its involvement on modifying both mRNA expression and protein levels of members of the MAPK family. Additionally, the expression of CDK4 gene was modulated within the cell response to Co-Cr-enriched medium, while the modulation in the expression of P15 and P21 indicates an important regulatory mechanism required. Overall, our results demonstrate that trace of CoCr elements triggers decisive intracellular signaling in shear-stressed endothelial cells, suggesting influence on angiogenesis-related mechanism and they bring novel insights to explain the biological activity of CoCr as it has been emerged as interesting biomedical materials within the medical and dentistry fields.
Keywords: Biomaterials; Blood vessel; Chromium; Cobalt; Endothelial cell; Implants